Enhancing Performance of Teachers through Peer Observation: A Critical Review for Implementation In Bangladeshi Colleges - Ashim Kumar Paul (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The research purpose of achieving quality education is that enhancing teachers' performance is a must since it determines students' learning and academic achievement. On the other hand, peer observation (PO) is a practical tool used in a classroom where two peers work together and observe each other's teaching, and accordingly, the observer gives constructive feedback to the observed teacher, helping bring about positive changes in the instruction. Therefore, this paper seeks to explore the effectiveness of peer observation and formulate a framework for its implementation for improving the teaching performance of Bangladeshi college teachers. In this regard, the researcher used a secondary data analysis method in which around 75 papers, including journal articles, conference proceedings, and research reports of different authors and organizations, were studied, analyzed, and discussed in this paper. Besides, two more case studies in international contexts were elaborate to review. After analyzing the documents, the researcher divided the issue into several themes and sub-themes. The result found that the PO's implementation would enhance the teachers' performance, and consequently, the students' success would be augmented. Later, deliberating on different PO models, an implementation plan for PO in Bangladeshi colleges context was devised and developed.